ANALISIS PROSES PRODUKSI BIOGAS KOTORAN SAPI DENGAN LIMBAH KULIT NANGKA SEBAGAI BAHAN BAKAR PENANAK NASI BIOGAS - Doddy Suanggana (Jurusan Teknik Mesin, Universitas Halu Oleo, 2022)
Analysis of Biogas Production Process of Cow-Dung Mixed with Jackfruit Skin Waste as Biogas Rice Cooker Fuel. Human needs cannot be separated from the need for fossil energy so that it will decrease as human needs increase. To minimize this, other alternative energy is needed such as biogas energy derived from organic materials and maintained continuity. From the research on the production process of cow dung and jackfruit skin waste, the values of temperature, mass, pressure and the amount of biogas mass consumption during cooking rice were obtained. The study was conducted using 3 experiments on a 30 liter digester with different ratios of cow dung, jackfruit skin waste and water, namely 25%: 50%: 25%; 37.5%: 37.5%: 25%; 50%: 25%: 25%. Data collection was carried out for 30 days at 10.00 WITA and 17.00 WITA. Based on the measurement results, it is known that the variation of 37.5%: 37.5%: 25% is the best variation compared to the variation of 25%: 50%: 25% and 50%: 25%: 25%. The daily pressure of c2 is 0.04 bar with a total mass of 21.4 grams. The average daily ambient temperature obtained is 30.27°C and the average digester temperature C2 is 30.74°C with a temperature not exceeding mesophilic conditions. The biogas production in the C2 digester was intermittent for 30 days which was then used to carry out a cooking test of 8.1 grams of rice for 13.06 minutes. Keywords: Biogas, Energy, Jackfruit skin waste, Cow dung.